Preparation of highly purified ω-3 docosapentaenoic acid from seal oil via urea complexation combined with preparative high performance liquid chromatography. Issue 10 (3rd July 2021) - Mu, Hongyan; Li, Xiaodan; Jin, Qingzhe; Sun, Qingjie
ABSTRACT: Docosapentaenoic acid (DPA) derived from seal oil was concentrated by urea complexation and purified by preparative high performance liquid chromatography (pre-HPLC). A Box-Behnken Design (BBD) combined with response surface methodology (RSM) was applied to optimize urea complexation conditions. The maximum concentration of DPA (12.75%) with the yield of 48.54% were obtained at the FFA/Urea ratio of 1:3.7 (g/g) and crystallized at 1.3°C for 17.5 h. The concentrates were further fractionated by isocratic elution with the mixture of methanol and 0.1% aqueous phosphate on a C18 column, giving rise to a DPA purity to 93.12% with the yield of 38.37%. The present study could provide useful information and the highly purified products would contribute their beneficial effects for food and nutraceutical applications.